Analysis Of Farming Business And Income Contribution Of Cassava Farmers - Amalinda Harahap, Fitri; Firdauzi, Indrawan; Saputro, Wahyu Adi (Universitas Djuanda, 2024)
Cassava is an alternative food besides rice and corn. Farmers cultivate cassava as an additional alternative in their farming business. One of the locations that has good cassava production in Central Java is Banyumas Regency, precisely in Cilongok District. Many farmers in Cilongok cultivate cassava because it is easier to care for and there is already a market for it, especially for entrepreneurs in the surrounding area who buy farmers' harvests. This study aims to analyze the farming business and income contribution of cassava farmers in Banyumas. The method used in this study is quantitative descriptive. The selected sample was 30 cassava farmers in Cilongok District, Banyumas. The data analysis method is farming business analysis and calculation of income contribution. Based on the results of the study, it is known that the average cassava production in Cilongok District reaches 6,218 kilograms per hectare. Cassava farmers also have a cassava farming business income of Rp 2,831,150. The contribution of cassava income to farmers in Cilongok District reaches 20.77 percent.